2015
DOI: 10.1038/srep17383
|View full text |Cite
|
Sign up to set email alerts
|

RBFOX3/NeuN is Required for Hippocampal Circuit Balance and Function

Abstract: RBFOX3 mutations are linked to epilepsy and cognitive impairments, but the underlying pathophysiology of these disorders is poorly understood. Here we report replication of human symptoms in a mouse model with disrupted Rbfox3. Rbfox3 knockout mice displayed increased seizure susceptibility and decreased anxiety-related behaviors. Focusing on hippocampal phenotypes, we found Rbfox3 knockout mice showed increased expression of plasticity genes Egr4 and Arc, and the synaptic transmission and plasticity were defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 47 publications
3
68
0
Order By: Relevance
“…EGR4 is also upregulated in response to trophic factors in an ERK1/2-dependent manner that has been characterized in the context of neuronal development and spermatogenesis [65-67]. While EGR4 appears to compensate for EGR1 in some cases, SRF binding to the EGR4 promoter was shown to occur in neuronal cells [68] supported by indirect evidence that serum may regulate the EGR4 promoter generated in Jurkat T cells [69].…”
Section: Regulation Of Egr Expressionmentioning
confidence: 99%
“…EGR4 is also upregulated in response to trophic factors in an ERK1/2-dependent manner that has been characterized in the context of neuronal development and spermatogenesis [65-67]. While EGR4 appears to compensate for EGR1 in some cases, SRF binding to the EGR4 promoter was shown to occur in neuronal cells [68] supported by indirect evidence that serum may regulate the EGR4 promoter generated in Jurkat T cells [69].…”
Section: Regulation Of Egr Expressionmentioning
confidence: 99%
“…Real-time quantitative PCR was performed using SYBRgreen on a TAKARA detection system (TAKARA, Shiga, Japan) under the conditions recommended by the manufacturer. The primer sequences were as follows (27)(28)(29)(30)(31)(32)(33): angiotensinogen (Agt, NM_007428), forward: 5'-GGC CGC CGA GAA GCT AGA-3' and reverse: 5'-GGC TGG CCG TGG GAT CTA-3'; renin (Renin, NM_031192), forward: 5'-GCC GCC TCT ACC TTG CTT GTG-3' and reverse: 5' GGG GCA GCT CGG TGA CCT CT-3'; angiotensin I converting enzyme (Ace, NM_207624), forward: 5'-AGG GAA CAT GTG GGC GCA GAC-3' and reverse: 5'-CGG TGG GCT TCT CTA ACA TCG A-3'; advanced glycosylation end product-specific receptor (Ager, NM_007425), forward: 5'-TGA GGA GAG GAA GGC CCC G-3' and reverse: 5'-GCC ATC ACA CAG GCT CGA TC-3'; neuronal nuclei (NeuN, NM_001039167), as a marker of neural cells, forward: 5'-GAG GAG TGG CCC GTT CTG-3' and reverse: 5'-AGG CGG AGG AGG GTACTG-3'; glial fibrillary acidic protein (Gfap, NM_010277) , as a marker of astrocytes, forward: 5'-GAA CAA CCT GGC TGC GTA TA-3' and reverse: 5'-GCG ATT CAA CCT TTC TCT CC-3'; cluster of differentiation molecule 11b (CD11b, NM_001082960), as a marker of microglial cells, forward: 5'-GAT CAA CAA TGT GAC CGT ATG-3' and reverse: 5'-GAT CCC GGA AAT TGG AGT GAG-3'; glyceraldehyde 3-phosphate dehydrogenase (Gapdh, NM_008084), forward: 5'-CCG CAT CTT CTT GTG CAG TGC C-3' and reverse: 5'-GGG GTC GTT GAT GGC AAC AAT CTC-3'.…”
Section: Animals Male Diabetic Mice [C57blks(bks) Cg-+ Lepr Db /+mentioning
confidence: 99%
“…4b and S3). To further examine a role for Rbfox3 in Snord116 splicing, we utilized a published dataset of RNA sequencing from Rbfox3 knockout mouse cerebral cortex (24). Visualization of exon junctions within the Snord116 locus by sashimi plot using the IGV browser demonstrated that loss of Rbfox3 leads to pronounced dysregulation of exon splicing between Snord116 and Ube3a (Fig.…”
Section: Neuron-specific Splicing Of Transgenic Snord116 Requires Rbfmentioning
confidence: 99%
“…RNA-seq Analysis SRA files were downloaded from GEO (GSE84786) (24) and converted to fastq files using fastq-dump, splitting files for paired-end reads. Reads were trimmed for adapters and quality using the following parameters: ILLUMINACLIP:TruSeq3-PE.fa:2:30:10:8:T LEADING:15 TRAILING:15 SLIDINGWINDOW:4:15.…”
Section: Inverse Pcr Primers: F -Gatttccaagtctccaccccat; R -Ggctatgaamentioning
confidence: 99%